Far-Infrared-Emitting Sericite Board Upregulates Endothelial Nitric Oxide Synthase Activity through Increasing Biosynthesis of Tetrahydrobiopterin in Endothelial Cells. (31st October 2019) - Kim, Seonhee; Lee, Ikjun; Song, Hee-Jung; Choi, Su-jeong; Nagar, Harsha; Kim, Sung-min; Jeon, Byeong Hwa; Kim, Book Sung; Park, Hyun Jong; Piao, Shuyu; Kim, Cuk-Seong
Abstract : Far-infrared ray (FIR) therapy has been reported to exert beneficial effects on cardiovascular function by elevating endothelial nitric oxide synthesis (eNOS) activity and nitric oxide (NO) production. Tetrahydrobiopterin (BH4 ) is a key determinant of eNOS-dependent NO synthesis in vascular endothelial cells. However, whether BH4 synthesis is associated with the effects of FIR on eNOS/NO production has not yet been investigated. In this study, we investigated the effects of FIR on BH4 -dependent eNOS/NO production and vascular function. We used FIR-emitting sericite boards as an experimental material and placed human umbilical vein endothelial cells (HUVECs) and Sprague–Dawley rats on the boards with or without FIR irradiation and then evaluated vascular relaxation by detecting NO generation, BH4 synthesis, and Akt/eNOS activation. Our results showed that FIR radiation significantly enhanced Akt/eNOS phosphorylation and NO production in human endothelial cells and aorta tissues. FIR can also induce BH4 storage by elevating levels of enzymes (e.g., guanosine triphosphate cyclohydrolase-1, 6-pyruvoyl tetrahydrobiopterin synthase, sepiapterin reductase, and dihydrofolate reductase), which ultimately results in NO production. These results indicate that FIR upregulated eNOS-dependent NO generation via BH4 synthesis and Akt phosphorylation, which contributes to the regulation of vascular function. This might develop potential clinical application of FIR to treat vascular diseases by augmenting the BH4 /NO pathway.